\\ log_2(-x) = 0 => -x = 1 => x = -1\\log_2(-x) = 2 => -x = 4 => x = -4\\" alt="\sqrt{2log_2(-x)} - log_2\sqrt{x^2} = 0\\\sqrt{2log_2(-x)} = log_2|x|\\\left \{ {{2log_2(-x) = log_2^2|x|\\} \atop {log_2|x| \geq 0 }} \right. \\\left \{ {{2log_2(-x) = log^2_2(-x)} \atop {|x| \geq 1}} \right. \\\left \{ {{log_2(-x)(log_2(-x)-2) = 0} \atop {|x|\geq 1}} \right. => \\ log_2(-x) = 0 => -x = 1 => x = -1\\log_2(-x) = 2 => -x = 4 => x = -4\\" align="absmiddle" class="latex-formula">
с учетом ограничений, вызванных возведением в квадрат, корней остается прежнее количество.
Ответ: x = -4, -1